Studi Koordinasi Proteksi Arus Lebih Fasa Dan Gangguan Tanah Pada Jaringan Distribusi Berbasiskan Digsilent Powerfactory - Putra, Randy; Hasyim Rosma, Iswadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Distribution Network is one of the parts in a power system that has an important role because it deals directly with users, especially the users of medium and low voltage level. Therefore it needs a protection system against abnormal condition to maintain the reliability of the system. The protective equipment analyzed in this article is the overcurrent relay (OCR) and ground fault relay (GFR). The aim of the article is to determine the settings of OCR and GFR protection devices. By calculating the short circuit, the current and time settings of OCR and GFR can be determined. The short circuit current was simulated by using DigSILENT PowerFactory. It has been found from the results that time setting is influenced by value of short circuit current. The higher the fault current the the faster the trip time of the protection devices. Keywords: Short Circuit, Protection, Relay Setting, DigSILENT